Impact of Covid-19 Pandemic on Mses and Cooperatives and Strategic Recovery in New Normal Era (Jurnal Manajemen dan Organisasi, 2021)
The purpose of this study is to examine the economic impact of Covid-19 on the performance of micro, and small enterprises (MSEs) and cooperative institutions; how the strategies and formulate a recovery strategy in the new normal era. The main data used are primary data collected through interviews to MSE and microfinance institutions. The analytical method used is descriptive statistics and econometric models. The before and after analysis shows the significantly different costs and benefits of MSEs before and after the pandemic.  The analysis shows that in the pandemic Covid-19 period, all MSEs decreased performance, most experienced a decrease in business turnover (6 percent) and similarly with cooperative institutions, their turnover decreased to 55%. The strategy of the cooperatives to maintaining its performance is to provide relaxation, improve efficiency by reducing employees, and ask for a reduction in profit-sharing payments to creditors; while the MSE strategy if the cooperatives does not provide loans for a while is 60 percent of MSEs seeking loans from relatives, 25 percent borrowing from other microfinance despite high-interest rates and 15 percent selling their household assets.